Teleoperadoras ativas: estresse e expressividade oral - Pimentel, Aline Tavares (2007)
Background: the professional voice, the verbal behavior and the mode as the communication interpersonal can be define the relations of job. To relate the verbal expressivity about stress, of form that if can think about who these aspects intervene is something recent in the speech-therapy. The telemarketing and the conditions of job have been explored in the research, the field of the professional voice. Objective: to investigate the relation between the symptoms of stress and the characteristics of verbal expressivity in active teleoperators of a central office of telemarketing of Salvador. Method: 52 teleoperators of the active sector had been selected, in the period between March and June of 2007. In this group, two protocols had been applied. First one investigated aspects about general health and the second the protocol approached aspects relative the occupational questions. Also the questionnaire Job Stress Scale for the verification was applied of stress in the work environment. Were select the records of the two teleoperators that had presented high consuming and low consuming for analyzes of the verbal expressivity for a speech therapy specialist in voice. Results: high consuming in 50% of the teleoperators was verified, haven t significance statistics between perception of the teleoperators and stress. The teleoperator with high consuming related great number of health problems. About your verbal expressivity this was positive, a time that presented intonations variations, adequate pauses and emphases and contextualized inflection. The teleoperator with low consuming, related little symptoms of health problems and about your verbal expressivity can be considered more negative, she show less emphases and phrases. Conclusion: The stress affected positively the verbal expressivity of the teleoperator with high consuming and refusal of the teleoperator with low consuming. Suggests work groups and discussion about stress inside the company, similar to increase the perception and assistant in the development of management for stress